The role of tolerance in the social and spiritual life of Uzbekistan (on the example of the medieval) - Odilov, A (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
For centuries, the territory of our country has been located at the crossroads of East and West trade and economic relations, and in turn, the ideas of different ethnic groups and religions have entered this land. In the socio-spiritual life of the Middle Ages, in turn, these circumstances led to the assimilation of the ideas of tolerance into the way of life of the population. This article for the first time analyzes the issue of ethnic and inter-religious tolerance in the socio-spiritual life of the country in the Middle Ages